Routledge Handbook of Athlete Welfare - Lang, M. (Routledge, 2021)
Athlete welfare should be of central importance in all sport. This comprehensive volume features cutting-edge research from around the world on issues that can compromise the welfare of athletes at all levels of sport and on the approaches taken by sports organisations to prevent and manage these.